If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + -12 = 4y + 24 Reorder the terms: -12 + -2y = 4y + 24 Reorder the terms: -12 + -2y = 24 + 4y Solving -12 + -2y = 24 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -12 + -2y + -4y = 24 + 4y + -4y Combine like terms: -2y + -4y = -6y -12 + -6y = 24 + 4y + -4y Combine like terms: 4y + -4y = 0 -12 + -6y = 24 + 0 -12 + -6y = 24 Add '12' to each side of the equation. -12 + 12 + -6y = 24 + 12 Combine like terms: -12 + 12 = 0 0 + -6y = 24 + 12 -6y = 24 + 12 Combine like terms: 24 + 12 = 36 -6y = 36 Divide each side by '-6'. y = -6 Simplifying y = -6
| -7(c+9)=9(c-5)-14c | | 10/3+8= | | k-31=5(1-7k) | | 4n+3=n-17 | | y^2=12y-35 | | 5y-1=2y+5 | | ABD=180(5y+1) | | 3not=6 | | s^2+45=0 | | 0.7=z+0.5 | | 5x-3=4(x+2) | | 4(1+4x)=30+3x | | -4(d-4)+2(d-2)=10/3 | | 12+3y=9 | | 6t-3=-7 | | 2(x-1)=48 | | a+7+3b+3a-2b= | | -2x-3-4+4x=-10x+3+5x | | 3x+7=x-13 | | 0.25(20+4p)-0.5(8+2p)= | | 19x-4=18x+2 | | 4x-12=3x+12 | | 7y=x+0 | | (59/6)-9=5/6 | | 3p-1=5(p-1)-2(7-2p) | | 4=y+13 | | -37-4a=-a+5(-6a-2) | | -2(-6+1)=-2 | | 240-22=-4(1-60) | | x=50+-2y | | h/10=-22/5 | | 7-3x=x+13 |